Fitorremediação do 2,4-diclorofenoxiacético (2,4-d) pelo Plectranthus neochilus - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The use of pesticides is aimed at increasing the production and quality of agricultural products. However, these compounds can cause harm to the environment and to humans due to their wide use and toxicity. 2,4-Dichlorophenoxyacetic (2,4-D) is a widely used herbicide for various crops in Brazil and the world to combat broadleaf weeds. It has characteristics of high solubility in water, mobility and persistence leading to contamination of water and soil and in its commercial formula, used in farming, it presents toxicological classification I (extremely toxic). Thus, for the recovery of areas contaminated with 2,4-D, the use of plants capable of degrading, stabilizing and /or removing contaminants, known as phytoremediation, becomes extremely important due to the low cost and plant diversity for this purpose. The present study evaluated the possible phytoremediation capacity of Plectranthus neochilus (boldo) exposed to the commercial pesticide (Aminol) in soil and water through consecutive extractions (interval of days). After this period, the plant's responses were analyzed in terms of the presence of 2,4-D in leaf tea, total antioxidant capacity (DPPH), total polyphenols and flavonoids analysis for plants exposed to soil and water. In the plants exposed in the water it was also verified the total antioxidant capacity by the phosphomolybdenum method and the quantification of phenolic compounds. After 15 days of experiment, 2,4-D was no longer detected in the soil samples and the plant was not necessary in the decontamination of this matrix due to degradation of the compound occurring in the same period. Differently, in water, 2,4-D remained up to 67% in 60 days of experiment, which provided the use of two treatment groups with the plant (a group of plants for 30 days and a new group in the remaining 30 days in the same system), and thus a decontamination of up to 49% of 2,4-D was obtained. The compound was not detected in tea leaves of the plant and total antioxidant capacity, polyphenols and flavonoids were decreased in soil (whole experiment) and water (first 30 days). However, for those plants that were in the water in the remaining 30 days, x there was an increase in these analyzes near the basal level (compared to blanc - plants in contact with water only). In the quantification of the phenolic compounds (caffeic acid, coumaric acid and ferulic acid) present in the tea of these plants, it was observed that in the group of plants of the first 30 days there was an increase of the coumaric acid and ferulic acid, compared to the group of plants not exposed to 2,4-D in treatment 1 and a decreased in caffeic acid in treatment 2. In the remaining 30 days with the new seedlings, there was a decrease of the coumaric acid and increase of the caffeic and ferulic acids (treatment 1 and 2). The results indicated that the plant had the capacity of phytoremediation of the 2,4-D in water and, although the compound caused damages in the antioxidant system, it obtained an increase of the quantified phenolic compounds, making tea of the plant useful after phytoremediation.
Keywords: Total antioxidant activity; Tea; Phenolic compounds; Total flavonoids; Total antioxidant activity; Plectranthus neochilus; Plectranthus neochilus; Bioquímica; Atividade antioxidante total; Chá; Polifenóis totais; Compostos fenólicos; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA